2021
DOI: 10.1002/ijc.33716
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of prevention strategies on cervical cancer incidence in South Africa

Abstract: In 2020, the World Health Organisation (WHO) published a strategy to eliminate cervical cancer as a public health concern. In South Africa, despite having a national screening policy in place since 2000, diagnosed cervical cancer incidence has shown no signs of decline. We extend a previously developed individual‐based model for human immunodeficiency virus (HIV) and human papillomavirus (HPV) infection to include progression to cervical cancer. The model accounts for future reductions in HIV incidence and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
(77 reference statements)
0
21
0
Order By: Relevance
“…15,17,18,26,32,34 Strategies combining HPV vaccination and primary HPV testing are predicted to be particularly effective in preventing cervical cancer. 24,33 A South African study compared cervical cell collection devices for cytology-based screening and found that the more expensive plastic brush would yield lower costs per woman screened than the wooden spatula because fewer smears would have to be repeated. 29 In a study on women living with HIV in Kenya, conventional VIA and HPV testing similarly reduced the number of cervical cancer cases and deaths because the effect of better diagnostic performance of HPV testing was balanced by minimized losses to follow-up through same-day treatment for VIA-positive women.…”
Section: Results Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…15,17,18,26,32,34 Strategies combining HPV vaccination and primary HPV testing are predicted to be particularly effective in preventing cervical cancer. 24,33 A South African study compared cervical cell collection devices for cytology-based screening and found that the more expensive plastic brush would yield lower costs per woman screened than the wooden spatula because fewer smears would have to be repeated. 29 In a study on women living with HIV in Kenya, conventional VIA and HPV testing similarly reduced the number of cervical cancer cases and deaths because the effect of better diagnostic performance of HPV testing was balanced by minimized losses to follow-up through same-day treatment for VIA-positive women.…”
Section: Results Of Included Studiesmentioning
confidence: 99%
“…Only 5 studies modeled HIV transmission-1 because it focused on the effectiveness of HIV control strategies on cervical cancer incidence and mortality, 23 and the other studies extended HIV and HPV transmission models to assess the impact of cervical prevention strategies. 24,27,31,33 If HIV disease progression was incorporated, this was mostly done by including CD4 cell count stages in the model, yet CD4 cell categories varied across studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations